If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = -5x + -3 Reorder the terms: -6 + 7x = -5x + -3 Reorder the terms: -6 + 7x = -3 + -5x Solving -6 + 7x = -3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6 + 7x + 5x = -3 + -5x + 5x Combine like terms: 7x + 5x = 12x -6 + 12x = -3 + -5x + 5x Combine like terms: -5x + 5x = 0 -6 + 12x = -3 + 0 -6 + 12x = -3 Add '6' to each side of the equation. -6 + 6 + 12x = -3 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = -3 + 6 12x = -3 + 6 Combine like terms: -3 + 6 = 3 12x = 3 Divide each side by '12'. x = 0.25 Simplifying x = 0.25
| 7(x+8)-14=28 | | .6x-7=7 | | 4x-80=0 | | 55x+3(9x+12)=-64 | | 0=16t^2+128t+144 | | x+3.8=9.2 | | 4p+2p+6p-1= | | 7x-20=29 | | Ma-Th=fun | | -10x+10=-10 | | (4x^2)(-2x^3y^5)(-3xy)=0 | | 5x*5x= | | r(x)=-0.11x^2+100x | | 5n-18=-33 | | -5x+-30=80 | | 3(5z-3)-3(-2z)=6 | | 2(x-1)=3x-(x+2) | | 6s-15=-6+5a | | 9t-22=-29+8t | | -11x-31=-20 | | .5y+7=.75y-4 | | 32=(x-7)(x+7) | | 5(6c-4)+3(8c-1)= | | 2(3+5x)-5=31 | | 74-4x=14x+24 | | 15-2(w+5)=11 | | X+24=130 | | 11x-31=-20 | | x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) | | 2x+12=90+3x+23 |